Evaluation of Grazing Options During Summer for Growing Heifers - J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2021)
Developing methods to provide high quality forage through a majority of the year is important for cattle operations. The purpose of this study was to determine forage management options to offset the summer “slump” with fescue. Four grass pasture treatments (10 pastures total; 4 acres) were used in a completely randomized design and stocked with growing heifers (n = 47; initial wt 419 ± 20 lb). Pasture treatments consisted of novel fescue (FES), crabgrass (CRAB), bermudagrass (BERM), and sorghum-sudan interseeded into novel fescue (SS-FES). Heifers were weighed and grazed FES/SS-FES pastures April to November (213 d) or CRAB and BERM May through September (131 d). Heifers on FES were continuously grazed. All other pastures were rotationally grazed. Average daily gain for the entire grazing period was greater for heifers on SS-FES as compared to all other grass treatments (P = 0.001). Between April and May, FES heifers had greater average daily gain (ADG) than SS-FES pastures (P = 0.001); yet, the heavier stocking rate resulted in similar gain per acre (P = 0.16). May to July ADG and gain per acre was greatest for BERM, followed by CRAB, with FES and SS-FES having the lowest gains (P<0.001). From July through September, ADG was greater for SS-FES and CRAB as compared to FES, with BERM intermediate (P = 0.03) while gain per acre was lowest for FES (P = 0.10). The ADG and gain per acre were greater for SS-FES than FES (P = 0.001) from late September to November. As a summer grazing option, warm season grass alternatives, either as the sole source of pasture or interseeded into fescue, are better options for gain as compared to fescue alone.
Keywords: interseeding warm-season annual; fescue; bermudagrass; cattle gain